2019
DOI: 10.1253/circj.cj-19-0376
|View full text |Cite
|
Sign up to set email alerts
|

Serum Matrix Metalloproteinase-9 Is Associated With Depression After Acute Ischemic Stroke

Abstract: Background: Matrix metalloproteinase-9 (MMP-9), a key determinant of extracellular matrix degradation, might cause cerebral damage after stroke and be involved in the development of depressive symptoms. This study aimed to evaluate the association of serum MMP-9 levels and post-stroke depression (PSD). Methods and Results: Serum MMP-9 levels were determined in 558 acute ischemic stroke patients from 7 hospitals comprising the China Antihypertensive Trial in Acute Ischemic Stroke. We assessed depression status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…MMP9 is the most investigated member of the matrix metalloproteinase family, which normally remodels the extracellular matrix and pathologically attacks substrates as part of the neuroinflammatory response. Previous studies from the China Antihypertensive Trial in Acute Ischemic Stroke reported a positive association of baseline MMP9 levels with the risk of poor functional outcome, poststroke cognitive impairment, and depression [10–12]. On the other hand, MMP9 was demonstrated to be regulated by some long noncoding RNAs through the ceRNA network [16], which was similar with our findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…MMP9 is the most investigated member of the matrix metalloproteinase family, which normally remodels the extracellular matrix and pathologically attacks substrates as part of the neuroinflammatory response. Previous studies from the China Antihypertensive Trial in Acute Ischemic Stroke reported a positive association of baseline MMP9 levels with the risk of poor functional outcome, poststroke cognitive impairment, and depression [10–12]. On the other hand, MMP9 was demonstrated to be regulated by some long noncoding RNAs through the ceRNA network [16], which was similar with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…circRNAs were demonstrated to be involved in the progression of ischemic stroke through the ceRNA network of circRNA-miRNA-mRNA. For instance, circDLGAP4 functioned as an endogenous miRNA-143 sponge to inhibit miRNA-143 activity, resulting in the inhibition of homologous to the E6-AP C-terminal domain E3 ubiquitin [10][11][12]. On the other hand, MMP9 was demonstrated to be regulated by some long noncoding RNAs through the ceRNA network [16], which was similar with our findings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a population of about 600 ischemic stroke patients and in a period of 3 months after the event, approximately 40% of the patient population were classified to have post-stroke depression symptoms, and the MMP-9 level in these patients (658.8 ng/mL on average) were much higher than those identified without post-stroke depression (485.7 ng/mL on average) [143]. Patients' blood samples were collected after a minimum of 8 h of fasting for MMP-9 measurements; MMP-9 serum was detected and measured using commercially available ELISA kits [143]. It was suggested that MMP-9 was also involved in cerebral damage following stroke events [143].…”
Section: Mps In Central Nervous System and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Patients' blood samples were collected after a minimum of 8 h of fasting for MMP-9 measurements; MMP-9 serum was detected and measured using commercially available ELISA kits [143]. It was suggested that MMP-9 was also involved in cerebral damage following stroke events [143].…”
Section: Mps In Central Nervous System and Neurodegenerative Diseasesmentioning
confidence: 99%